The Effect of Shopping Lifestyle and Fashion Involvement on Purchase Decision with Impulse Buying as an Intervening Variable In E-commerce Shopee - Ayu Sari Dewi; Aida Nursanti; Marhadi Marhadi; Mida Aprilina Tarigan (Universitas Riau, 2023)
This study aims to analyze the influence of shopping lifestyle and fashion involvement on purchasing decisions with impulse buying as an intervening variable on e-commerce shopee. This research was conducted on all consumers domiciled in Indonesia who had purchased products at Shopee e-commerce.In this study, it consists of four variables, namely one bound variable, one intervening variable, and two free variables. These variables are: Impulse Buying (Y2), Purchasing Decision (Y1), Fashion Involvement (X2), Shopping Lifestyle (X1). This study was conducted using a sample of 132 people with questionnaire crossing. The data analysis tool used for hypothesis testing is path analysis with a Partial Least Square (PLS) approach using the SmartPLS ver 3.0 software application. The results of this study state that: 1) shopping lifestyle has a positive and significant effect on impulse buying; 2) fashion involvement has a positive and significant effect on impulse buying; 3) Impulse buying has a positive and significant effect on the whiteness of the purchase; 4) shopping lifestyle has a positive and significant effect on purchasing options; 5) fashion involvement has a positive and significant effect on purchasing decisions; 6) shopping lifestyle has a positive and significant effect on purchasing decisions ventilated by impulse buying; 7) Fashion involvement has a positive and significant effect on purchasing decisions that are ventilated by impulse buying.